Capacity Enhancement Workshop on Gender and Climate Change Adaptation in Punjab, India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Training of Trainers and Workshop for rural women leaders on gender and climate change adaptation in Punjab, India. The ultimate aim is to empower women at the grassroots to understand that they are able to make choices that enable adaptation to climate change but require little financial or technological investment.